1999
DOI: 10.23986/afsci.5633
|View full text |Cite
|
Sign up to set email alerts
|

The environmental effectiveness of alternative agri-environmental policy reforms: theoretical and empirical analysis

Abstract: This paper analyzes alternative agri-environmental policy reforms to reduce nutrient runoff when the government has price support, fertilizer tax, buffer zone subsidy and acreage subsidy as available instruments. To promote environmental goals, the government is assumed to adjust the tax and subsidy rates so as to keep the farmer's profits constant. This instrument switch reduces the prices of lesspolluting inputs and the farmer re-optimizes his production so that it becomes more environmentally friendly. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…by Lankoski and Ollikainen 1999, Iho 2005and Helin et al 2006. However, the emphasis in these studies is in theoretical set-up and crop production and their results are not directly comparable to this study.…”
Section: Review Of Literaturecontrasting
confidence: 60%
“…by Lankoski and Ollikainen 1999, Iho 2005and Helin et al 2006. However, the emphasis in these studies is in theoretical set-up and crop production and their results are not directly comparable to this study.…”
Section: Review Of Literaturecontrasting
confidence: 60%
“…It may be noted that direct comparison between the abatement costs for a fertiliser tax that are reported in this study and estimates by Lankoski and Ollikainen (1999) and Vatn et al (1997) is difficult. The reason is that those studies reported the costs of reduced leaching as an amount of money per area unit while the measure used in the present study is an amount of money per concentration.…”
Section: Total and Marginal Abatement Costsmentioning
confidence: 74%
“…These figures are averages from three different study areas in southeastern Norway and varied somewhat depending on the area. Lankoski and Ollikainen (1999) simulated a 30% reduction in N-leaching in their study of alternative agri-environmental policy reforms in Finland. They found that a fertiliser tax is less efficient in reducing N-leaching than a buffer-strip subsidy.…”
Section: Introductionmentioning
confidence: 99%
“…The social abatement cost for Finnish fertiliser taxes, which are compensated for by an acreage subsidy, was estimated at FIM 24.7 (EUR 4.15) per abated kg N leaching using a Danish leakage function (the reduction in leaching was simulated to be 30%). According to the results, the use of buffer zones was a more cost efficient way to reduce leaching than fertiliser taxes (Lankoski and Ollikainen, 1999). In Norway, Vatn et al (1997) estimated the corresponding social marginal abatement cost to be about NOK 4/kg abated N leaching.…”
Section: Fact Box 4 Tax On Fertilisersmentioning
confidence: 99%